Pandangan dan Konsep Deradikalisasi Beragama Perspektif Nahdlatul Ulama (NU) - Mohammad Akmal Haris (Risâlah, Jurnal Pendidikan dan Studi Islam, 2020)
Abstract The rise of radicalism in the name of religion as both a school and a movement has become a serious concern of the Indonesian government in stemming it. The Indonesian government through the National Counterterrorism Agency (BNPT) is trying to take strategic steps in countering this radical movement, one of which is by cooperating with the Islamic organization Nahdlatul Ulama (NU). Nahdlatul Ulama as a moderate social organization, in addition to having a strong and extensive organizational network capital that can reach the grassroots, it is hoped that it will be very strategic in countering the spread of radical and extreme ideals in Indonesia. The concept of deradicalization applied by Nahdlatul Ulama is carried out in a persuasive manner by promoting a humanist approach in building dialogue within the internal Islamic community. For example, through the da'wah movement of NU scholars and kiai, through pesantren networks, through scientific studies such as bahtsul masail, NU online preaching media, and by fortifying the Aswaja based NU educational institution (Ahlussunah wal Jamaah). Keywords: deradicalization, religion, and Nahdlatul Ulama.